Biochemical and Histopathological Studies on the Water Extracts of Marjoram and Chicory Herbs and Their Mixture In Obese Rats - Ahmed, Lamiaa A.; Ramadan, Reham S.; Mohamed, Reham A. (Pakistan Journal of Nutrition, 2009)
The effects of water extract of marjoram, chicory or mixture of both on some biological, biochemical and histological factors of hyperlipidemic obese rats were studied. Forty adult female rats were distributed into eight groups, the first one was kept as negative control, while the other seven groups were fed on high fat diet for induction of obesity. One of these groups was kept as positive control while the left 6 groups were orally given daily by stomach tube the 1 ml of water extract of marjoram, chicory or mixture of both at 5% and 10%, for 4 weeks. Results showed that isoflavones content in chicory water extract was higher than that of marjoram water extract. Body weight gain was markedly lower especially in the chicory and in mixture of marjoram and chicory groups (5% and 10%) compared to high fat diet control group. Oral administration of marjoram, chicory or their mixture water extracts at 5% and 10% lowered concentrations of total cholesterol, triglycerides, LDL-c, VLDL-c and decreased activity of AST and ALT enzymes. Furthermore, all extracts caused significant increase in HDL-c and T3 hormone concentrations except marjoram groups. Histopathological examination showed amelioration of histopathological lesions seen in liver of obese rats received the water extract of chicory or mixture of both. This study recommends that intake of water extract the mixture of marjoram and chicory especially at 10% because it may be useful for treating obesity accompanied by hyperlipidemia.